Death-feigning behaviour in Iphisa elegans: the second reported case in the Family Gymnophthalmidae (Reptilia: Squamata) - Machado-Filho, Paulo Roberto [UNESP]; Moya, Guilherme Marson; Maffei, Fabio [UNESP] (Inst Nacional Pesquisas Amazonia, 2018)
Death-feigning behaviour occurs when the animal simulates a state of immobility. This behaviour is described for some lizard families, among them the family Gymnophthalmidae with only one record. Iphisa elegans is a diurnal and terrestrial Amazonian lizard, it has cryptic behavior and moves rapidly on the ground, hindering observations of its behavior. We report a case at the Comodoro Municipality, Mato Grosso State, Brazil: an adult male of I. elegans, when manipulated, turned its venter up and put itself in a death-feigning posture. This species is preyed by birds, snakes and other lizards, possibly behaving this way when the cryptic behaviour or scape attempt fails. More studies are necessary to observe the efficiency of this behaviour, as well as the frequency that it occurs, using individuals of both sexes. We also suggested to evaluate if the orange venter of males could have any antipredation advantage.
Keywords: Reptiles; Ethology; Antipredator Display; Lizard; Thanatosis